Linking the processes of medication administration to medication errors in the elderly - Emerentia C. Nicholson; Anneleen Damons (AOSIS, 2022)
Background:Older people are more prone to chronic diseases than younger ones and typically receive multiple medications. Medication rounds in long-term care facilities (LTCFs) are usually lengthy, with most errors occurring during the administration phase. How nurses apply medication administration processes can affect resident outcomes. Aim: To determine the processes of medication administration followed by nurses in LTCFs as self-reported by them to identify possible factors associated with medication errors. Setting: Twenty-eight LTCFs for the elderly in the Western Cape province, South Africa. Methods: A non-experimental cross-sectional descriptive design was applied, using a quantitative approach. A stratified sampling method obtained equal samples of nurses from funded and private LTCFs, thus N = 123 respondents. Data collection was via self-administered questionnaires. The Statistical Package for the Social Sciences (SPSS27) was used for descriptive and inferential analysis. Results: Nurses' self-reported medication errors such as the sharing of medication between residents (83%), the omission of doses (64.8%), neglecting to sign after medication administration (57%), and medication administered at the wrong time (50.8%). Frequent interruptions during medication rounds were the most common reason for medication errors (75.6%). Conclusion: Multiple medication administration process errors were self-reported by the nurses. LTCFs should provide mandatory medication training, monitor the adherence to correct medication administration procedures, and implement risk-management strategies. Contribution: The identified factors associated with medication errors during medication administration processes can assist with developing risk management strategies and policies in the LTCFs and improve evidence-based practice and resident outcomes.